Records of the Department of State relating to the internal affairs of Haiti, 1910-29 (National Archives, National Archives and Records Service, General Services Administration, 1965)
Consist mainly of instructions to and despatches from the U. S. diplomatic and consular officials; two African American diplomats were assigned to Haiti during this period: H. W. Furniss, envoy extraordinary and minister plenipotentiary in 1905-1913; L. W. Livingston, consul at Cap-Häitien in 1894-1919.